RESILIENSI MASYARAKAT ADAT BADUY DALAM MENGHADAPI TANTANGAN LINGKUNGAN - Prabowo, Hendro; Basuki, A. M. Heru; Ayuningsih, Aprilia Maharani (Jurnal Psikologi, 2024)
This research examines the resilience of Baduy indigenous community in facing environmental challenges caused by population growth and limited agricultural land. By using a case study approach, this research aims to understand the adaptive strategy applied by Baduy community to survive. The results show that the Baduy community utilizes an agricultural system based on customary values (pikukuh) and conducts bubuara (wandering) to find new land. The community also applies the transmission of customary values to the younger generation as an effort to maintain tradition and local wisdom. In conclusion, the resilience of Baduy community lies in their ability to adapt to environmental changes while still maintaining their cultural identity, which shows the importance of local wisdom in facing environmental challenges.